Committing the English and the continental way: An experiment - Christoph Engel; André Schmelzer (Max Planck Institute for Research on Collective Goods, 2017)
On the doctrinal surface, there is a deep divide between common and continental law when it comes to the origin of contractual obligations. Under continental law, in principle a unilateral promise suffices. Common law by contrast requires consideration. When it comes to deciding cases, the divide is much less pronounced. But for the most part the law does not govern people's lives through adjudication. It matches or molds their moral intuitions. We test these intuitions in the lab. If consideration is required, participants believe that all participants make more ambitious promises. But they themselves make a more cautious promise. These two effects cancel out, so that promises are not more likely to be kept with consideration.
Keywords: C91; D02; D03; D12; D64; H41; K12; 330; contract; obligation; promise; consideration; experiment; modified dictator game